2012
DOI: 10.1038/ncomms2125
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric phosphorus deposition may cause lakes to revert from phosphorus limitation back to nitrogen limitation

Abstract: Recent findings indicate that increased atmospheric deposition of nitrogen of human origin has caused changes in the pattern of ecological nutrient limitation in lakes in the northern hemisphere. An increase in the nitrogen to phosphorus ratio, and hence a shift from pristine nitrogen limitation to human-induced phosphorus limitation of phytoplankton growth, seems to have been driven by deposition of atmospheric nitrogen. These findings challenge the classical paradigm of lake phytoplankton productivity being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 23 publications
(24 reference statements)
6
99
0
Order By: Relevance
“…14.5). In an opposite way, the concentration of dissolved inorganic nitrogen has decreased with time in the lakes (Camarero and Catalan 2012).…”
Section: Effects Of Airborne Nutrients On Ecosystemsmentioning
confidence: 99%
See 3 more Smart Citations
“…14.5). In an opposite way, the concentration of dissolved inorganic nitrogen has decreased with time in the lakes (Camarero and Catalan 2012).…”
Section: Effects Of Airborne Nutrients On Ecosystemsmentioning
confidence: 99%
“…Phosphorus comes largely from South, accompanying the dust outbreaks reaching the Pyrenees from Northern Africa and the Iberian Peninsula (Camarero and Catalan 2012). There is a certain correlation between the North Atlantic Oscillation (NAO) index and the production of dust in Northern Africa and subsequent transport towards the Mediterranean (Moulin et al 1997).…”
Section: Effects Of Airborne Nutrients On Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bergström and Jansson (2006) have shown that increased N deposition may have changed lakes from N-limitation to P-limitation in remote and small lakes across the northern hemisphere, an observation supported by nutrient addition experiments in UK upland streams (Maberly et al 2002). On the other hand, an assessment of long-term data from a Spanish ILTER lake site by Camarero and Catalan (2012) suggested that atmospheric P deposition may cause lakes to revert from P-limitation to N-limitation. There are clear needs for research into longterm C-N-P interactions for a much wider range of biomes.…”
Section: Complex Interactions Of N With Other Elementsmentioning
confidence: 96%